Fungal virulence at the time of the end-Permian biosphere crisis? - Visscher,H; Sephton,MA; Looy,CV (GEOLOGY, 2011)
Throughout the world, latest Permian records of organic-walled microfossils are characterized by the common presence of remains of fi lamentous organisms, usually referred to the palynomorph genus Reduviasporonites. Although generally regarded as indicators of global ecological crisis, fundamental controversy still exists over the biological and ecological identity of the remains. Both fungal and algal affinities have been proposed. We seek to resolve this enigma by demonstrating close morphological similarity of the microfossils to resting structures (monilioid hyphae, sclerotia) of Rhizoctonia, a modern complex of soil-borne filamentous fungi that includes ubiquitous plant pathogens. By analogy with present-day forest decline, these findings suggest that fungal virulence may have been a significant contributing factor to widespread devastation of arboreal vegetation at the close of the Permian Period.